The Investigation of Porcelain Plates Roughness Influence on Determination of Explosives Friction Sensitivity - Sonia Nachlik; Mateusz Pytlik (Applied Sciences)
The influence of the roughness of porcelain plates on the results of the friction sensitivity test of explosives was investigated. For this purpose, the roughness of selected batches of plates from several manufacturers (Julius Peters, OZM Research s.r.o., Deltima Precision s.r.o.) was determined. Subsequently, according to the standards EN 13631-3:2005 and STANAG 4487 JAIS (edition 2), friction sensitivity tests of PETN (Pentaerythritol Tetranitrate, penthrite) and RDX (Royal Demolition Explosive, hexogen) were carried out. No statistically significant correlation was established under the experimental conditions—although sanded plates had the lowest roughness (mean value 5.07 μm) and simultaneously gave the lowest sensitivity results (168 N for RDX and 80 N for PETN according to the EN 13631-3 while 216 N for RDX and 121 N for PETN according to the STANAG 4487), Julius Peters plates with a similar level of roughness (mean value 6.07 μm) did not reflect the pattern and results of the sensitivity tests that were surprisingly high (120 N for RDX and 64 N for PETN according to the EN 13631-3 while 182 N for RDX and 67 N for PETN according to the STANAG 4487). Due to these results, the human factor is indicated as a key factor in the obtained discrepancies; however, further research in this matter may be needed.